Social Institutions and State Policy in Indonesia’s Interfaith Marriage Regulation - Resty, Marhalisa Eka; Fithriyyah, Mustiqowati Ummul (Fakultas Syariah INSURI Ponorogo, 2026)
This study situates interfaith marriage within the broader context of Indonesia's plural society and the increasing use of alternative legal mechanisms to analyze negotiations among social institutions, state law, and religious law. The objective is to identify points of convergence and normative conflict in regulating interfaith marriage and to assess their implications for legal certainty and citizens' rights. The research applies a normative legal method grounded in legal pluralism, based on doctrinal analysis of statutory regulations, Constitutional Court decisions, Supreme Court Circular Letter Number 2 of 2023, and the Compilation of Islamic Law. The findings show that normative tension stems from differing interpretations of Article 2 of the 1974 Marriage Law and the prohibition of interfaith marriage under positive Islamic law, reinforced by judicial policy and administrative barriers to registration. These conditions create socio-religious pressure and encourage strategies such as marrying abroad or exploiting procedural loopholes. The study concludes that interfaith marriage exists within a legal gray zone shaped by power relations among the state, religious authorities, and social actors, highlighting the need for inclusive reform, legal harmonization, and responsive public services within Indonesia's plural legal system.